Stability of T-DNA Integration in Phalaenopsis “Sogo Vivien” Transgenic Orchid Carrying 35S::Gal4::AtRKD4::GR - Endang Semiarti; Exsyupransia Mursyanti; Ahmad Suyoko; Faiza Senja Widya Perdana; Catharina Tri Widyastuti; Aditya Nur Subchan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2018)
Orchid is an elegant ornamental plant and favoured by the society. Phalaenopsis